Some computational aspects of homogenization of thermopiezoelectric composites - Gałka, Andrzej; Telega, Józef Joachim; Wojnar, Ryszard (Computer Assisted Methods in Engineering and Science; Vol 3 No 2 (1996), 2023)
On the basis of the paper [1] two topics are discussed. Firstly, exact formulae for the homogenized coefficients of a layered thermopiezoelectric composite are derived. Secondly, by applying the Ritz method, the local problems are solved approximately. Specific cases are also examined and illustrated.